Development of Catalytic-CVD SiNx Passivation Process for AlGaN/GaN-on-Si HEMTs - Myoung-Jin Kang; Hyun-Seop Kim; Ho-Young Cha; Kwang-Seok Seo (Crystals, 2020)
We optimized a silicon nitride (SiNx) passivation process using a catalytic-chemical vapor deposition (Cat-CVD) system to suppress the current collapse phenomenon of AlGaN/GaN-on-Si high electron mobility transistors (HEMTs). The optimized Cat-CVD SiNx film exhibited a high film density of 2.7 g/cm3 with a low wet etch rate (buffered oxide etchant (BOE) 10:1) of 2 nm/min and a breakdown field of 8.2 MV/cm. The AlGaN/GaN-on-Si HEMT fabricated by the optimized Cat-CVD SiNx passivation process, which had a gate length of 1.5 μm and a source-to-drain distance of 6 μm, exhibited the maximum drain current density of 670 mA/mm and the maximum transconductance of 162 mS/mm with negligible hysteresis. We found that the optimized SiNx film had positive charges, which were responsible for suppressing the current collapse phenomenon.